Full genome based sequence and structural characterization of an unusual group A rotavirus G12P[11] isolated from neonates in Pune, western India. Issue 10 (28th February 2020) - Ranshing, Sujata S.; Cherian, Sarah S.; Agarwal, Megha S.; Jagtap, Anuradha S.; Patil, Chinmayee M.; Gopalkrishna, Varanasi
Highlights: NIV-1740121 G12P[11] exhibited Wa-like genotype constellation. The strain might have undergone multiple-gene reassortment events. Localized charge changes in VP7 may affect interaction with neutralizing antibodies. Type I glycan binds G12P[11] VP8* in similar pattern at the same active site as N155. Abstract: Studies conducted at neonatal intensive care units in Pune, western India, suggested early exposure to rotaviruses and predominance of unusual human–bovine-like G12P[11] strains. The whole genome sequencing and phylogenetic analyses of a naturally attenuated, culture adapted neonatal strain, (NIV-1740121) revealed multiple-gene reassortment events, containing ROTAVAC® vaccine strain, 116E-like VP4, VP6, NSP3, NSP5 genes, VP7 gene of G12 origin and VP3 gene of porcine ancestry in a human Wa-like backbone. Analysis of 3D structure modeling of the VP7 and VP4 proteins with respect to 116E suggested amino acid variations in the major neutralizing epitopes of VP7, contributed to a modified charge density. Visualization of receptor-glycan interaction structures of NIV-1740121 and 116E VP8* showed type I glycan binds with a similar conformation at the same active site as represented in the available crystal structure of G10P[11] VP8*. The study adds to the knowledge of age restricted tropism of P[11] strains in neonates.